DIVIDEND POLICY IN INDONESIAN BANKS: THE EFFECT OF FOREIGN OWNERSHIP, INSTITUTIONAL OWNERSHIP, AND INDEPENDENT COMMISSIONERS - Susanto, Ian Himawan; Inayati, Nur Isna; Fakhruddin, Iwan; Pratama, Bima Cinintya (Juremi: Jurnal Riset Ekonomi, 2023)
This study aims to find empirical evidence of the influence of foreign ownership, institutional ownership and independent commissioners on dividend policy. The population in this study is all banking sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Sample selection using purposive sampling method and obtained 103 observational data from 41 banking sector companies listed on the Indonesia Stock Exchange (IDX) during five years of observation. Hypothesis testing using multiple linear regression analysis. The results of this study show that foreign ownership has a negative and significant effect on dividend policy, institutional ownership has a positive and significant effect on dividend policy, independent commissioners have no effect and are not significant on dividend policy.